Alpha‐Linolenic Acid Supplementation Improves Testosterone Production in an Aged Breeder Rooster Model: Role of Mitochondrial Modulation and SIRT1 Activation - Long, Cheng; Zhao, Zhi‐xian; Willing, Benjamin P.; Sheng, Xi‐Hui; Wang, Xiang‐Guo; Xiao, Long‐Fei; Qi, Xiao‐Long (Molecular nutrition & food research, 2024)
Scope Aging in males can lead to declines in testosterone production, essential for maintaining male reproductive health. Methods and results To investigate the effects of dietary supplementation with alpha‐linolenic acid (ALA) on testosterone production in aged breeder roosters and understand the underlying molecular mechanisms involved. An in vivo model is established to investigate the effects of dietary ALA supplementation on testosterone production in aged breeder roosters, and the Leydig cell culture is used to identify the potential molecular mechanism. Dietary supplementation with ALA increases in plasma testosterone. Congruently, ALA supplementation enhances the expression of testosterone biosynthesis‐related enzymes. ALA supplementation exerts anti‐apoptotic effects in testicular mitochondria, as evidenced by a lower expression of pro‐apoptotic factors and a higher expression of the anti‐apoptotic factor B‐cell lymphoma 2 (Bcl‐2). Moreover, In Leydig cells, ALA supplementation promotes mitochondrial biogenesis genes. The proposed mechanism is that ALA activates the sirtuin1 (SIRT1) pathway and is supported by higher SIRT1 transcript and protein in Leydig cells. Furthermore, blocking SIRT1 with siRNA reverses ALA's effects on testosterone biosynthesis and mitochondrial function‐related genes. Conclusion These findings indicate that dietary supplementation with ALA can improve testosterone production in aged breeder roosters, possibly by modulation of mitochondrial function via activating the SIRT1 pathway. ALA promotes testosterone production and the expression of testosterone biosynthesis‐related enzymes StAR, P450scc, and 3β‐HSD in rooster testis and its Leydig cells by activating the SIRT1 pathway. ALA enhances expressions of mitochondrial biogenesis regulatory factors PGC‐1α, NRF1, and TFAM in Leydig cells by activating the SIRT1 pathway.